(untitled) (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2021)
This study analyses the South American experiences, socio-cultural analyses and the commitment to Latin American peoples in the second half of the twentieth century, that characterize the lives of Linda Bimbi, general secretary of the Lelio Basso International Foundation, and Alberto Manzi, the “teacher of Italy”. A parallelism founded by the presence in their writings of different a-centric themes that represent indispensable tools for interpreting the specificities of the Latin American world, such as respect for the rights of peoples, liberation theology, educational mission, the role of the church.